RAPID ASSESSMENT ON BIODIVERSITY IN LOGGED FOREST OF TESSO NILO, RIAU PROVINCE, SUMATRA - Prawiradilaga, Dewi M.; ., Purwaningsih; Susiarti, Siti; Sidik, Irvan; Suyanto, A.; Rachmatika, Ike; Noerdjito, Woro A.; Marakarmah, A.; Sinaga, M. H.; Cholik, E.; Saim, A. (Perhimpunan Biologi Indonesia, 2014)
Tesso Nilo area which is located at Riau province covers an area of 188.00 ha. Recently, it is famous because of asharply increased in encroachment activities for forest conversion, especially for oil palm plantations and villagesites. It was conducted in logged forest around Segati river, Toro river, Mamahan river and Sawan river in June2003. The results showed that the area had the high richness of plant species which was indicated by the high valueof Mennhenick index. Records from the 1 ha studied plot identified a total of 360 species included 165 genera and57 families with 215 tree species 305 sapling species. Some important tree species which were included in the RedList of IUCN were â??gaharuâ?? (Aquilaria malaccensis), â??raminâ?? (Gonystylus bancanus), Shorea spp. and Dipterocarpusspp. The local community utilized 83 species of medicinal plants and 4 species of toxic plants for fishing. The totalnumber of recorded bird species was 114 species represented 29% of the total Sumatran bird species. The mostimportant bird species were the Wrinkled Hornbill (Aceros corrugatus), Crestless Fireback (Lophuraerythrophthalma), Crested Fireback (Lophura ignita) and Hooked-billed Bulbul (Setornis criniger). The total numberof recorded mammal species was 34 species or 16.5% of 206 species of Sumatran mammals. The most importantmammal species included Sumatran tiger (Panthera tigris sumatrae), Sumatran elephant (Elephas maximussumatrensis), the Sun bear (Helarctos malayanus) and three species of primates: Hylobates agilis, Presbytis femoralisand Macaca nemestrina. The herpetofauna contained 15 reptile species and 18 amphibian species. The mostimportant herpetofauna was the endangered False Gharial (Tomistoma schlegelii) and the vulnerable Common Softshelledturtle (Amyda cartilaginea). The number of recorded fish species was 50 represented 18% of the totalSumatran fish species (272 species). The important fish species were Breinsteinea sp. and Chaca bankanensis whichwere unique and rare. Since insects are the largest group of animal, this study only focused on beetles. Theidentified beetles were classified into 644 species and 34 families. The important beetles were the Longhorn beetles(Cerambycidae) and the Scarab beetles (Scarabaeidae).The small mammal parasites consisted of ectoparasites whichwere categorized into 14 species and endoparasites which were categorized into 2 orders and 3 species.Keywords: biodiversity, logged forest, richness, Sumatran tiger, Sumatran elephant